2020
DOI: 10.1002/chem.202001504
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of a Potent α‐Thrombin Binding Aptamer Incorporating Hexitol Nucleotides

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…For all the oligonucleotides, a sigmoidal decrease of the absorbance at 295 nm was found upon increasing the temperature (Figure 2, panel c and d, respectively for the K + -and Na + -rich buffers), in agreement with the unfolding of the G4 domain [66,69,70], while the heating processes monitored at 260 nm (Figure S8, panel a and b, respectively for the K + -and Na + -rich buffers) produced hyperchromic effects upon melting, as generally observed for duplex unfolding [49][50][51]68].…”
Section: Uv Spectroscopy Analysis: Thermal Difference Spectra and Uv Thermal Denaturation/renaturation Measurementssupporting
confidence: 81%
See 2 more Smart Citations
“…For all the oligonucleotides, a sigmoidal decrease of the absorbance at 295 nm was found upon increasing the temperature (Figure 2, panel c and d, respectively for the K + -and Na + -rich buffers), in agreement with the unfolding of the G4 domain [66,69,70], while the heating processes monitored at 260 nm (Figure S8, panel a and b, respectively for the K + -and Na + -rich buffers) produced hyperchromic effects upon melting, as generally observed for duplex unfolding [49][50][51]68].…”
Section: Uv Spectroscopy Analysis: Thermal Difference Spectra and Uv Thermal Denaturation/renaturation Measurementssupporting
confidence: 81%
“…Then, UV-monitored thermal denaturation/renaturation experiments were performed to study the thermal stability of both the G-quadruplex and duplex domains of the cyclic NU172 analogues in comparison with NU172 and its "nude" G4 motif NU. It was previously shown, in fact, that the UV-melting curves monitored at 295 and 260 nm give information respectively on the unfolding of the G-quadruplex and duplex domains of the bimodular aptamers [49][50][51]68].…”
Section: Uv Spectroscopy Analysis: Thermal Difference Spectra and Uv Thermal Denaturation/renaturation Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the challenges associated with the short in vivo half-life, recently, De Fenza et al incorporated some of the critical NU172 nucleotides (at the T9 and G18 positions) with hexitol-based nucleotides to assess their effect on NU172 anticoagulant activity, binding affinity, and plasma half-life [ 48 ]. They found that incorporating these bases slightly improved the NU172 anticoagulant properties.…”
Section: Extrinsic and Common Pathway Aptamersmentioning
confidence: 99%
“…Our approach exploits the well-known finding that the quality of host-guest interactions benefits from the increase in the preorganization of the guest, since no entropy penalty is involved in the binding process. As demonstrative examples, conformationally restricted nucleosides bearing a six-membered sugar unit have already been found to hold an excellent biomimetic potential in various therapeutic contexts [ 38 , 39 ], as a result of the resemblance of natural ribofuranosyl nucleosides in their bioactive conformations [ 40 ]. Accordingly, following our longstanding interest in the identification of conformationally restricted molecules with biomimetic properties [ 39 , 41 , 42 , 43 , 44 , 45 , 46 ], we undertook the synthesis of novel Immucillin-A and Immucillin-H analogues, i.e., polyhydroxylated piperidine nucleosides 3 and 4 ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%